Analisis Semiotik terhadap Kebebasan Berpendapat di Film Aum! - Achmad, Rivenskly Fahreza; Kusuma, Ade (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Movies depict the reality in which they are made. Movies can be used as a medium of communication from the filmmaker to convey messages in the form of ideas, thoughts or concerns about a particular matter. Director Bambang Kuntara Murti's from film call “Aum!” tells the story of the challenges experienced by independent filmmakers who went through the film production process during the “Orde Baru” era. This research uses a qualitative approach with the semiotic method of Roland Barthes, aiming to see how nationalism and freedom of speech during the early reformation period in the movie entitled “Aum!”. The results of this study show the efforts of the characters in the film, which is how activists tried to convey criticism of the new order government through a work of a film. The films they made were a form of the struggle of young people at that time to convey their voices and criticize the policies of the authorities. Movies became a medium to convey resistance to oppressive rulers. This movie with drama and action genres also educates the public that how to show the value of nationalism can be in any way according to their respective creativity. Keywords: films, Freedom of Speech, Nationalism, Semiotic